2015
DOI: 10.5897/ijfa14.0444
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of bacteria load in fish species of commercial importance at the Aquaculture Unit and Lagoon Front of the University of Lagos

Abstract: Bacteria diseases are widespread and can be of particular importance in fish farming. Bacteria exist as micro flora in water until certain environmental conditions such as poor water quality occur, which could impose a stress on fish, thereby making them vulnerable to infection, most especially by pathogenic bacteria. This study was carried out to assess and compare the bacteria diversities and population in Clarias gariepinus, Sarotherodon melanotheron and Oreochromis niloticus, in the three grow out ponds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 4 publications
4
8
0
Order By: Relevance
“…The highly infected part of the examined° C. gariepinus used for bacteriological studies was the skin compared to the intestine, this may be due to the fact that the skin is always in contact with the surrounding water and also, the skin may get contaminated with bacteria during handling. This observation agrees with the work of [17] who recorded high bacterial loads on the skin of fresh Tilapia fish (Oreochromis niloticus) when compared with the intestines and gills; Adebayo -Tayo et al [18] also made similar observation but this observation was in contrary to the work of Olugbojo et al [19] who reported high population of bacteria in the gut of three fish species sampled in Lagos State; likewise [20] and [21], also reported high bacterial loads in the intestine part of African Catfish.…”
Section: The Results Of This Research Work Is Represented Insupporting
confidence: 90%
“…The highly infected part of the examined° C. gariepinus used for bacteriological studies was the skin compared to the intestine, this may be due to the fact that the skin is always in contact with the surrounding water and also, the skin may get contaminated with bacteria during handling. This observation agrees with the work of [17] who recorded high bacterial loads on the skin of fresh Tilapia fish (Oreochromis niloticus) when compared with the intestines and gills; Adebayo -Tayo et al [18] also made similar observation but this observation was in contrary to the work of Olugbojo et al [19] who reported high population of bacteria in the gut of three fish species sampled in Lagos State; likewise [20] and [21], also reported high bacterial loads in the intestine part of African Catfish.…”
Section: The Results Of This Research Work Is Represented Insupporting
confidence: 90%
“…The total bacteria count load in the gut of G. elegans fish was higher than in the gut of A. marmid and other types of fish as shown in Table (4). [13] explained that the total bacteria count in fish that exceeds 8 91 making them unfit for consumption therefore, the results of the present study can not be considered as a risk to the consumer. The contamination observed may result from rupturing fish gut during poor processing or inadequate washing agent for food spoilage [14].…”
Section: Issn: 1813 -1662 (Print) E-issn: 2415 -1726 (On Line)mentioning
confidence: 96%
“…and Enterococcus spp. as recorded by Aboyadak et al [4], Zhang et al [5], Olugbojo and Ayoola [6], Darak and Barde [7], Thune et al [8].…”
Section: Introductionmentioning
confidence: 98%